C3-Symmetric Pyridine and Bipyridine Derivatives: Simple Preparation by Cyclocondensation and 2D Self-Assembly at a Solution–Graphite Interface - Dash, Jyotirmayee; Trawny, Daniel; Rabe, Jürgen P.; Reissig, Hans-Ulrich (Synlett, 2015)
The efficient preparation of four C3-symmetric (star-shaped) pyridine and bipyridine derivatives is reported. The key steps are Suzuki couplings of 4-pyridyl nonaflates with 4-acetyl-phenylboronic acid followed by an acid-promoted cyclocondensation reaction converting the methyl ketone moiety into the central benzene ring of the target compounds. Based on STM studies at a graphite–solution interface the two-dimensional arrangements of the compounds are discussed, showing the influence of the pyridine substitution pattern.
Keywords: allenes; heterocycles; cyclization; coupling; self-assembly; scanning tunneling microscopy; highly oriented pyrolytic graphite